Principles of construction of a purposeful psychological influence on the teens’ ability development to confront the criminalization - Кіраль, А. Й. (Київський національний університет імені Тараса Шевченка, 2017)
The article focuses on the importance of forming the ability to confront the criminalization in the younger generation. A generalization is made on the importance of finding out the integral personality characteristic of a teenager who is capable of lawful behavior in various life situations, including the cases of criminogenic temptations. There is a close connection between the ability of adolescents to confront criminality and their primary (patience, time, tenderness, trust, hope) and secondary (cleanliness, honesty, obedience, politeness, culture of behavior with money, justice) relevant abilities, an ability to solve the conflict situations creatively and take an attitude to the others from the parents. We have distinguished the types of adolescents’ ability to confront the criminalization, depending on the degree of its connection with behavioral features: emotional and intuitive, executive, communicative, prudent, and optimistic.

У статті акцентується увага на важливості формування у підростаючого покоління здатності до протистояння криміналізації. Зроблене узагальнення про важливість з’ясування цілісної характеристики особистості підлітка, здатної до правомірної поведінки у різних життєвих ситуаціях, у тому числі й у випадках криміногенних спокус. Констатується тісний зв’язок здатності підлітків до протистояння криміналізації з їх первинними (терпіння, час, ніжність, довіра, надія) та вторинними (охайність, чесність, послух, ввічливість, культура поведінки з грошима, справедливість) актуальними здібностями, здатністю творчо вирішувати конфліктні ситуації та перейнятим від батьків ставленням до оточуючих. Виокремлюються типи здатності підлітків до протистояння криміналізації в залежності від міри її зв’язку з поведінковими особливостями: емоційно-інтуїтивний; виконавчий; комунікативний; розсудливий; оптимістичний.
Принципи побудови цілеспрямованого психологічного впливу на формування здатності підлітків до протистояння криміналізації
Keywords: adolescents; ability to confront criminality; behavioral features; conflict respondings; lawful behavior; підлітки; здатність до протистояння криміналізації; поведінкові особливості; способи реагування на конфлікти; правомірна поведінка